Flora of endophytic fungi from roots and leaves of Azadirachta Indica and impact of culture media on their isolation from different sites Of Jabalpur region of central India. - Abid Hussain Qureshi; Sajad Ahmad Mir; Prof. Akhilesh Kumar Pandey; Shoket Ali (International Journal of Pharma and Bio Sciences, 2020)
Azadirachta indica (neem) is native of India and is well known for having ethnomedicinal properties. Aim of our study is to study various endophytic fungi isolated from different parts of plant, viz., leaves and root. Different and suitable medias was used to isolate the maximum number of endophytic fungi. Three different individual trees (at locations-Ax1, Ax2, Ax3) were used for isolation of endophytic fungi. Mycological agar (MCA) medium yielded the highest number of isolates. Highest number of isolated endophytic fungi were hyphomycetes, some Coelomycetes as well as Ascomycetes and very few from Zygomycetes class. Acremoniumacutatum was found to be dominant amongst all isolated endophytic fungi from root f A. indica, while C.cladosporioides showed dominance from the leaves of neem plant. A. acutatum showed highest dominance amongst isolated endophytic fungi from the root of the plant that accounts to 14.56% while Humicolagrisea showed zero dominance. A.acutatum and A.denii showed highest dominance of 11.32% while C.globosum, C.lunata and Nigrosporaoryzaeshowed zero dominance among the isolated endophytic fungi from leavesofA. indica.